Investigating the effects of two weaning methods and two genetic hybrids on play behavior in weaner pigs (Sus scrofa) - Franchi, Guilherme A.; Larsen, Mona L. V.; Winters, Jeanet F. M.; Jensen, Margit Bak; Pedersen, Lene Juul (Frontiers in Animal Science, 2022)
In conventional pig production, suckling pigs are typically weaned between 3–5 weeks of age. This involves separation from the sow, dietary change, and regrouping in a novel environment, which challenge the welfare of pigs. We investigated the effects of two weaning methods [conventional weaning: two litters mixed in a weaner pen of different size and design (MOVE) vs. litter staying in the farrowing pen after removing the sow (STAY)] and two genetic hybrids [DanBred Yorkshire × Landrace (approximately 21 total pigs born/litter; DB) vs. Topigs Norsvin TN70 Yorkshire × Landrace (approximately 16 total pigs born/litter with higher individual birth weight and weaning weight than DB; TN)] on play behaviour across weaning. Both genetic hybrids were inseminated with semen of DanBred Duroc boars. Litters were reduced to the number of functional teats at birth. The durations of locomotor-rotational play (LOC) and social play (SOC) of 24 indoor-housed litters [pigs/litter: (average±SD) 13±2; age at the weaning day: 26±2 d] were video-recorded continuously between 14:00 h and 22:00 h on days -1, 1 and 2 relative to weaning and statistically analysed with mixed-effects modelling at individual level. Before weaning, TN pigs performed LOC longer than DB pigs. On day 2 post-weaning, STAY pigs engaged in more SOC than MOVE pigs. Moreover, TN pigs and STAY pigs displayed a steeper increase in LOC from days 1 to 2 than DB pigs and MOVE pigs, respectively. We demonstrated that pigs belonging to the genetic hybrid with higher weight at birth and weaning spent more time playing on the day before weaning. Additionally, weaning pigs in the farrowing pen and, hence, avoiding social mixing and relocation to an unfamiliar environment, had a positive effect on social play after weaning. Our study illustrates that weaning stress in pigs may be reduced by using a genetic hybrid featuring higher birth and weaning weight and by keeping litters intact in a familiar environment after weaning. This study also supports the use of play behaviour as an animal welfare indicator.